2021
DOI: 10.1002/ece3.7100
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the links between habitat complexity and biodiversity in a kelp‐dominated subantarctic community

Abstract: Habitat complexity is one of the most important factors modulating species diversity. This feature comprises several interrelated attributes, such as number, size, and spatial arrangement of complexity‐forming elements. However, the separate and joint effects of these attributes on diversity and community structure are still not well understood. Here, we assess the relationships between several structural‐complexity attributes of the subantarctic kelp Lessonia flavicans and species richness, total abundance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Consistent with this, seaweed's fractal dimensions have been also shown to have an influence on invertebrate abundance and taxon richness (Mancuso et al, 2023a) regardless of host identity (Veiga et al, 2014). However, some studies have also found mixed results, with strong positive correlations between community structure and algal complexity features such as holdfast diameter and frond length, and negative correlations with features such as the number of stipes (Velasco-Charpentier et al, 2021).…”
Section: The Influence Of Individual Seaweed Featuresmentioning
confidence: 79%
See 2 more Smart Citations
“…Consistent with this, seaweed's fractal dimensions have been also shown to have an influence on invertebrate abundance and taxon richness (Mancuso et al, 2023a) regardless of host identity (Veiga et al, 2014). However, some studies have also found mixed results, with strong positive correlations between community structure and algal complexity features such as holdfast diameter and frond length, and negative correlations with features such as the number of stipes (Velasco-Charpentier et al, 2021).…”
Section: The Influence Of Individual Seaweed Featuresmentioning
confidence: 79%
“…While those increases range widely from weak to very strong, and the influence of non-native seaweeds or other factors add an additional level of complexity (e.g., Veiga et al, 2016;Lutz et al, 2019;Ndhlovu et al, 2021;Lenzo et al, 2023), seaweeds generally improve rather than hinder associated communities. The most consistent promoter of faunal diversity seems to be the complexity of identifiable features within a seaweed itself (e.g., branching or holdfast morphology; Hacker and Steneck, 1990;Hauser et al, 2006;Lutz et al, 2019: Velasco-Charpentier et al, 2021 or the complexity achieved by the presence of several individuals or species coming together into a discernable habitat (Best et al, 2014;Tano et al, 2016). Algal structural complexitybiodiversity relationships have also been examined using fractal dimensions, and the outcome of several key studies have provided added support to these relationships (e.g., Mancuso et al, 2023b).…”
Section: Implications For Conservation Restoration and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant in the Magellanic Province, in the Southeast Pacific ( Aldea et al 2011 ; Velasco‐Charpentier et al 2021 ) and with records in the South Atlantic ( Eliot 1907 ; Odhner 1926 , 1944 ), Pacific Ocean ( Marcus 1959 ; Meyers-Muñoz et al 2009 ; Schrödl 1996a , 2003 ), and Indian Ocean ( Odhner 1944 ).…”
Section: Resultsmentioning
confidence: 94%